(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
This article analyzes the situation of child labor in the early years of the First Brazilian Republic, focusing on Rio de Janeiro between 1890 and 1917, as well as the process of constructing legislation aimed at its regulation. It seeks to examine the forms of violence experienced by these minors and the impacts of early labor on their lives, in addition to understanding the principles that guided the formulation of such laws. The legislation is shown to have been shaped by philanthropic, humanitarian, and moralizing conceptions, while also resulting from the demands, mobilizations, and pressures of the working class for effective regulation and enforcement.